(untitled) (ModaPalavra e-periódico, 2011)
Of consumer segments, the women’s fashion is one of the most intriguing, as there is a perception that women are widely consumed, especially when it comes to fashion products. But there are those who, having committed a crime and being away from contact with society, they experience different situations of the majority. In this context, this study seeks to understand the relationship that the prisoners in Rio do Sul set the fashion world, compared to their status as social exclusion. To this end, we applied a questionnaire with closed questions and conducted interviews with two inmates. From analysis of quantitative and qualitative data, we can observe that the firms, for their situation in prison, have difficulty in obtaining of fashion items, and establish different relationships with this scenario and using the products of women with different goals socialize with "normal".